Pemanfaatan Aplikasi Berbasis Android BukuKas - Ningrum, Tinezia Angelina Puspa; Latifah, Nunuk; Rahmawati, Ika (Journal of Academia Perspectives, 2023)
The use of Information and Communication Technology (ICT) is currently an important requirement for the business sector to facilitate operational activities, including recording financial reports. Information systems are products of ICT development in the form of computer application programs that record and record data to make it easier for users or users to re-access and process data. Digital recording provides convenience and simplicity in its use to prepare financial reports and avoid recording errors. Various financial recording application systems are provided by online application service providers, one of which is the Cash Book. The purpose of using the BukuKas Application for the Bird Feed Caterpillar Breeding business was chosen because previously the business owner was still recording income and expenses perfunctorily, so many expenses were not recorded, so the owner had difficulty checking how much the collectors owed for purchases made. Business owners also find it difficult to record income and expenses because evidence/receipts are lost. Therefore, an information system is needed that helps record transactions safely and quickly by using the BukuKas application to facilitate recording activities and as a medium for recording business transactions. This type of research was conducted using a qualitative descriptive method. Data collection techniques include interviews, WhatsApp, and observation to observe the use of recording before and after using the application so that the selected application can produce a better business report.